The dehydration effect on mechanical properties of tooth enamel. (July 2019) - Hua, L.C.; Wang, W.Y.; Swain, M.V.; Zhu, C.L.; Huang, H.B.; Du, J.K.; Zhou, Z.R.
Abstract: Exploring the subtle mechanical property changes of tooth enamel in different conditions is important for dental research. However, some experimental results can be deceptive and may lead to misunderstanding. In particular, we show the dehydration associated with increased mechanical properties of tooth enamel as monitored by Nanomechanical System Testing (NST) can be misleading. The results indicate that the friction coefficient decreased with an increase of hardness of enamel upon dehydration, which appears to imply that dehydrated enamel has better mechanical properties than hydrated enamel. However, more critical scrutiny of the actual situation, suggests dehydrated teeth enamel are more prone to damage and greater wear. To appreciate the basis for the contrast between the experimental results and reality of natural hydrated enamel, which has better resistance to wear, and is critical for an understanding of the aetiology of enamel resistance to fracture.